COVID‐19 and hospice community palliative care in New Zealand: A qualitative study. (11th April 2022) - Frey, Rosemary; Balmer, Deborah
Abstract: Within the context of an ageing population and the added challenges posed by COVID‐19, the need to optimise palliative care management in the community – the setting where a significant proportion of people prefer to die – cannot be underestimated. To date, there has been a dearth of research exploring community palliative care delivery during the pandemic. This study aimed to explore the impact of and response to COVID‐19 for hospice community services in Aotearoa/New Zealand. Eighteen structured interviews were conducted (10 February–18 August 2021) with healthcare professionals from sixteen purposively sampled community hospices from New Zealand regions according to the number of COVID‐19‐positive patients per 100, 000 inhabitants (low, medium and high) with oversampling of high prevalence areas. Two overarching themes emerged 'challenges' and 'adaptations'. Each theme had several subthemes related to service delivery in communication, visiting, allied health team collaboration and volunteer services. Adaptations involved adjusting official health advice to the local context, increased use of telehealth, reducing infection risk during in‐home visits through triaging of cases, division of the workforce into teams and repurposing volunteers' services. Despite these adaptations, challenges remained, including increased workload pressures for staff and an absence of the human touch for patients and families. Implications for hospice practice and recommendations for future research are discussed. Governments must acknowledge the essential contribution of hospice to the COVID‐19 pandemic and ensure that these services are incorporated into the healthcare system response.